CFD prediction of coupled radiation heat transfer and soot production in turbulent flames - Bressloff, N. W. (Cranfield University, 1996)
The mechanisms governing the formation and destruction of soot in turbulent combustion are intimately coupled to thermal radiation due to the strong dependence of sooting processes and radiative loss on temperature. Detailed computational fluid dynamics (CFD) predictions of the radiative and soot output from turbulent non-premixed flames are normally performed by parabolic algorithms. However, the modelling of combustion systems, such as furnaces and unwanted enclosure fires, often require a fully elliptic description of the flow field and its related physical phenomena. Thus, this thesis investigates the intimate coupling between radiative energy exchange and the mechanisms governing soot formation and destruction within a three-dimensional, general curvilinear CFD code. Thermal radiation is modelled by the discrete transfer radiation model (DTRM). Special emphasis is given to approximate solutions to the radiative transfer equation encompassing various models for the radiative properties of gases and soot. A new algorithm is presented, entitled the differential total absorptivity (DTA) solution, which, unlike alternative solutions, incorporates the source temperature dependence of absorption. Additionally, a weighted sum of gray gases (WSGG) solution is described which includes the treatment of gray boundaries. Whilst the DTA solution is particularly recommended for systems comprising large temperature differences, the WSGG solution is deemed most appropriate for numerical simulation of lower temperature diffusion flames, due to its significant time advantage. The coupling between radiative loss and soot concentration is investigated via a multiple laminar flamelet concept applied within the CFD simulation of confined turbulent diffusion flames burning methane in air at 1 and 3 atm. Flamelet families are employed relating individual sooting mechanisms to the level of radiative loss, which is evaluated by the DTRM formulated for emitting-absorbing mixtures of soot, C02 and H20. Combustion heat release is described by an eddy break-up concept linked to the k-c turbulence model, whilst temperature is evaluated from the solved enthalpy field. Detailed comparisons between prediction and experiment for the critical properties of mixture fraction, temperature and soot volume fraction demonstrate the effectiveness of this novel, coupled strategy within an elliptic flow field calculation.